2015
DOI: 10.1016/j.bir.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The implied volatility index: Is ‘investor fear gauge’ or ‘forward-looking’?

Abstract: The paper aims to examine implied volatility as the investor fear gauge or/and forward-looking expectation of future stock market volatility within emerging markets setting-India VIX. The earliest results evidenced that VIX is the gauge of investor fear, where in the expected stock market volatility rises when the given market is declined. It is also proven that expected volatility is being unbiased estimate of the actual return volatility (30-calendar days); hence, during the market turmoil VIX likely to be b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 47 publications
2
14
0
1
Order By: Relevance
“…The energy market volatility index used in this study was constructed by the CBOE (the Chicago Board Options Exchange) while the EMV-ID was developed by Baker et al (2020). The former has been empirically tested over time and studies have established a negative correlation between the volatility index and market returns (see Bouri et al, 2018;Shaikh & Padhi, 2015). The EMV-ID, however, is still relatively recent and therefore has not received much empirical applications compared to other volatility indexes.…”
Section: Data and Methodology Data And Methodologymentioning
confidence: 99%
“…The energy market volatility index used in this study was constructed by the CBOE (the Chicago Board Options Exchange) while the EMV-ID was developed by Baker et al (2020). The former has been empirically tested over time and studies have established a negative correlation between the volatility index and market returns (see Bouri et al, 2018;Shaikh & Padhi, 2015). The EMV-ID, however, is still relatively recent and therefore has not received much empirical applications compared to other volatility indexes.…”
Section: Data and Methodology Data And Methodologymentioning
confidence: 99%
“…It was designed to measure the market’s aggregate expectation of future 30-day volatility ( Chow, Jiang, & Li, 2014 ). VIX is estimated out of the trading prices of the options written on equity index ( Shaikh & Padhi, 2015 ) and does not require a specific model, only current option prices ( Britten-Jones & Neuberger, 2000 ; Jiang & Tian, 2005 ). Accordingly, VIX is a simple and broadly used index (often dubbed the “fear index”) that provides theoretical and empirical support for decisions taken by CBOE.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Zheng (2014) determined there is a negative nexus between stock market sentiment and returns in the commodity market. Shaikh and Padhi (2015) found that VIX is a gauge for evaluating investors' fear of market decline and anticipation of increases in stock market volatility. Smales (2017) showed sentimentality has a greater impact on returns during crisis periods.…”
Section: Literaturementioning
confidence: 99%